AN ANALYSIS OF CULTURAL CONTENT OF ENGLISH TEXTBOOK FOR TENTH GRADE SENIOR HIGH SCHOOL - Sania, Mita; Cahyani, Fibria; Priastuti, Dyah Nugraheny (IKIP Widya Darma, 2023)
This study aimed to discover aspects of cultural content and describe how the culture is represented in English textbooks using descriptive qualitative method with content analysis. The data were collected from the English textbook